PREDICTING HEART FAILURE IN PATIENTS WITH DIABETES MELLITUS: GALECTIN-3, SST2, AND CAROTID THICKNESS - Herashchenko, A.S.; Fedorov, S.V.; Bielinskyi, M.V.; Seredyuk, N.M.; Kozlova, I.V. (World of Medicine and Biology, 2023)
Heart failure and Type 2 Diabetes Mellitus are two of the most common chronic conditions affecting adults worldwide. Soluble suppression of tumorigenicity 2 and galectin-3 are two biomarkers that have been studied extensively in recent years as predictors of risk of heart failure in patients with Type 2 Diabetes Mellitus. Carotid Intima Media Thickness is a well-established measure of arterial stiffness and vascular aging. We enrolled 154 patients with diabetes mellitus who presented to a private medical clinic: 83 patients in the diabetes mellitus with heart failure group and 71 patients in the diabetes mellitus–only group. We found that the diabetes mellitus with heart failure group had a significantly higher body mass index, mean Carotid Intima Media Thickness, and Galectin-3 compared to the diabetes mellitus group. However, there was no significant difference in age, gender composition, left ventricular ejection fraction, HbA1c, and soluble suppression of tumorigenicity 2 levels between the two groups.